MAKNA BUDAYA DALAM LIRIK LAGU RANUP KARYA RAFLI KANDE: KAJIAN ETNOLINGUISTIK - Herlina, Ninin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2020)
This research is an ethnolinguistic study that discusses how the lingual form and cultural meaning in the lyrics of the song 'Ranup' by Rafli Kande, an Acehnese artist. The research objectives are detailed, among others; 1) to describe the lingual forms in Ranup's song lyrics, 2) to interpret the cultural meaning in Ranup's song lyrics. This study uses a qualitative approach with descriptive type methods. The data collection method is done by using documentation. The data analysis method used in this research is the intralingual matching method and the estralingual matching method. The data analysis technique in this research is done by; 1) identifying data, 2) classifying data, 3) interpreting data. Presentation of the analysis results in this study using informal methods and formal methods. The results of this study are as follows: (1) the lingual form in the Ranup song lyrics is in the form of words, phrases, clauses, sentences, and discourses. (2) the cultural meaning contained in the lyrics of the Ranup song is the cultural meaning of respect, the meaning of sacred culture, the cultural meaning of conveying kindness, the cultural meaning of guidance, the cultural meaning of togetherness.